PENGARUH MOTIVASI EKSTERNAL, KOMPENSASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DI HOTEL SANTIKA TAMAN MINI INDONESIA INDAH - Jamaludin Khalid; Evan Rianto (LPPM Universitas Asa Indonesia, 2020)
The aim of this study is to analyze the effect of external motivation, compensation, and work discipline on emlployes performance both partially and simultaneously at The Hotel Santika Taman Mini Indonesia Indah. The sample used was 92 respondents using saturated sampling method. This data collection method uses a questionner that has been tested its vakidity and reliability. The analysis technique uses multiple linear regression, F test, t test, coefficient conrelation and determination. The result of this study prove that external motivation, compensation, and work discipline are partially and simultaneously have the positive effect on employees’s performance.